2022
DOI: 10.3389/fphar.2021.806844
|View full text |Cite
|
Sign up to set email alerts
|

P. granatum Peel Polysaccharides Ameliorate Imiquimod-Induced Psoriasis-Like Dermatitis in Mice via Suppression of NF-κB and STAT3 Pathways

Abstract: Psoriasis is a chronic and refractory inflammatory and autoimmune-mediated cutaneous disease affecting approximately 2%–3% of the global population. Most of the current therapies could relieve symptoms rapidly, while the side effects cannot be negligible. Hence, it is urgent to explore much safer and more effective treatments. In the current work, we evaluated the potential beneficial effect of Punica granatum peel polysaccharides (PPPs) in an imiquimod-elicited psoriasis-like mouse model and unraveled their m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 50 publications
(50 reference statements)
0
4
0
Order By: Relevance
“…Therefore, we hypothesize that linseed oil enhanced skin barrier function in obese mice by another factor. In addition, the epidermal thickening and proliferation of Ki-67 positive cells observed in the Control group are consistent with an earlier study, which showed increased Tnfα levels [16], as well as skin barrier dysfunction, in inflamed skin. Furthermore, skin inflammation in the context of obesity is also associated with increased Tnfα expression [25].…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, we hypothesize that linseed oil enhanced skin barrier function in obese mice by another factor. In addition, the epidermal thickening and proliferation of Ki-67 positive cells observed in the Control group are consistent with an earlier study, which showed increased Tnfα levels [16], as well as skin barrier dysfunction, in inflamed skin. Furthermore, skin inflammation in the context of obesity is also associated with increased Tnfα expression [25].…”
Section: Discussionsupporting
confidence: 92%
“…Excessive UVB irradiation can cause the excessive secretion and up-regulation of inflammatory signalling factors such as TNF-α, IL-1β and IL-8 in keratinocytes [ 15 ], leading to skin inflammation, which in turn affects the normal function of the skin barrier, leading to skin homeostasis imbalance, dry and red appearance, and desquamation [ 16 , 17 ]. In the epidermis, KLK-7 [ 38 ], FLG, caspase 14 [ 39 ] and AQP3 [ 40 ] are proteins closely related to the skin barrier that can help the keratinocytes maintain good skin barrier function. The abnormal activation of KLK-7 affects the barrier function of the stratum corneum [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Corresponding results were seen in the pathological evaluation, revealing that epidermal thickness was significantly increased by citrinin administration. Psoriasis is characterized as excessive inflammatory cytokine production and destruction of the skin barrier function (Chen et al, 2021). As the present study focused on the early development of psoriasis, TEWL as a barometer of skin barrier function was not so enhanced only by the imiquimod treatment, whereas citrinin exposure significantly enhanced the TEWL compared with the vehicle treatment.…”
Section: Discussionmentioning
confidence: 99%